2020
DOI: 10.1093/jbcr/iraa072
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Early Postoperative Range of Motion in Burn Patients With Newly Placed Hand Autografts: A Pilot Study

Abstract: Abstract Patients who suffer hand burns are at a high contracture risk, partly due to numerous cutaneous functional units, or contracture risk areas, located within the hand. Patients who undergo split-thickness skin grafting are often immobilized postoperatively for graft protection. Recent practice at our burn center includes an early range of motion (EROM) following hand grafting to limit unnecessary immobilization. The purpose of this study was to determine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…They started early ROM on POD 1 or 2 after skin grafting. In this report, this method was safe without increased incidence of skin graft loss [13]. In addition, there was no graft loss due to early postoperative exercises (Fig.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…They started early ROM on POD 1 or 2 after skin grafting. In this report, this method was safe without increased incidence of skin graft loss [13]. In addition, there was no graft loss due to early postoperative exercises (Fig.…”
Section: Discussionmentioning
confidence: 49%
“…Notably, the exercises of the hand and forearm are important [13]. Usually, active and passive exercises of the hand and forearm are initiated after the uptake of skin grafts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…133 Similarly, protocolized early range of motion for dorsal hand grafts may improve functional recovery without impacting graft take. 134 The popularization of negative-pressure wound therapy as a bolster dressing has improved outcomes over high-mobility areas, 135 in both meshed and sheet autografts, 136 using both commercial devices or more cost-effective alternatives. 137 Some centers are demonstrating the safety and costeffectiveness of outpatient burn surgery, 138 and incorporating home negative-pressure wound where graft loss from small hematomas or seromas will have significant functional or aesthetic consequences, allograft can be used to stage a closure between excision and sheet autografting.…”
Section: Postoperative Carementioning
confidence: 99%
“…Inability to achieve burn rehabilitation goals Decades of research have demonstrated the benefits of early splinting followed by aggressive mobility and range of motion therapy for healed burns/grafts near joints [ 36 ]. Recent literature indicates that early mobilization after grafting to the lower extremities and the hand is not associated with a significant increase in graft shear/graft loss [ 37 ]. Therefore, while peripheral nerve blocks in the extremities have the ability to completely anesthetize the area, this needs to be weighed against early mobility/therapy goals.…”
Section: Reviewmentioning
confidence: 99%